Comparative advantages of school and workplace environment in competence acquisition: Empirical evidence from a survey among professional tertiary education and training students in Switzerland - Thomas Bolli; Ursula Renold (ETH Zurich, KOF Swiss Economic Institute, 2015)
This paper sheds light on the questions how important competences are and which competences can best be learned at school and which competences can be acquired better in the workplace. Exploiting data from a survey among professional tertiary education and training business administration students and their employers in Switzerland, we find that competences related to strategic management, human resource management, organizational design and project management processes are most suitable to be taught in school. However, the results further suggest that soft skills can be acquired more effectively in the workplace than at school. The only exceptions are analytical thinking, joy of learning and organizational competences, for which school and workplace are similarly suitable. Thereby, the paper provides empirical evidence regarding the optimal choice of the learning place for both human resource managers as well as educational decision makers who aim to combine education and training, e.g. in an apprenticeship.
Keywords: A23; I21; 330; Competences; soft skills; school; workplace learning; relevance; learning place